The Inventory of the Estate farm Senkoniai - Pamerneckis, Stasys; Sakalauskaitė, Roberta (Lietuvos istorijos studijos, 2005)
The geometrical (land measuring) inventory of the Estate farm Senkoniai, which once belonged to the Karpis family and is kept at the Manuscript Department of Vilnius University Library, is being presented in this summary. It is characterized by the relative sufficiency of data about peasant farms, minuteness of description, and the addition of 12 land plans in good condition. The land plans were being drawn earlier, during the time of GDL, as well. The earliest of them were found at the same Manuscript Department from GDL Slavonic districts, dated 1789. One of them (No 13) is being presented here as an example. The inventory is written in Polish and is called "land measuring" (mierczy), i.e., the quantity of the land and its quality (whether it is a humus, a humus with loam, a sandy loam), its purpose (whether it is arable, used as a hayfield, a pasture, grown with bushes, a forest, or it is barren land) is indicated in it. Part of the land was designated for gardening and hop growing. The arable land, belonging both to the estate and to the peasants, was sectioned according to the traditional three-field system. The estate’s fields were mostly in one place, whereas the peasants’ fields, to their inconvenience, were not always situated near their villages; they were also in other places, as conditioned by the age-long stripped land system (rėžinė valstiečių ūkių sistema). In total, there were 8578.06 margas or 402.73 valakas of land in the estate, including the Estate farm Senkoniai, which had 522.79 margas (25.95 valakas), and the small Estate farm of Čeniškiai, which had 152.06 margas (7.14 valakas). The proportion of estate and peasant land, given in the inventory, is 1:12.7 in favor of the peasants, and as indicated by historiography, is reputed to be the most favorable among the other estates in the first half of the 19th century in Lithuania. In total, there are 15 villages with 80 peasant households of all categories (except the Estate farm Senkoniai) presented in the inventory. Because of its stripped land system denotation and marking of the strips of land in the plans, this inventory is regarded as a historical rarity. Besides the estate, the following data are presented in the inventory: 1) The category of each peasant household, the number of men and women in the household, their names, family dependence, age, hired persons, their names, and age. 2) Cattle belonging to the household, their breed and category. 3) The category of each household’s owned land, its quality, including the three-field system sections. 4) The quantity of crops in all the three fields. 5) The peasants’ duties to the estate: monetary, performing one’s corvée (eiti lažą), paying by work and in kind (mokėti darbu ir natūra). 6) The quantity of estate horses, bulls, and crops given to farms; besides, the number of inns in the estate farm is also indicated. There is a summary of all peasant households’ and the estate’s data at the end. All the twelve plans are in good condition and inserted, except the last one with the frayed borders. According to the authors of this survey, the scale of the land plans is given in valakas 1:6, because the scale has 5 divisions and their number 30 is given at the end, although a rope as the basis of the scale is clearly defined in the land plans dated 1789. There is evidence of one main principle in all the land plans: there is the land of one or two villages with the farms pictured in each plan, also two villages with the land beyond the margin (užusienio žemė), and the farms in one of the plans. Next, the three fields, situated near the estate farms and villages, are marked by the letters A, B, and C, while additional areas, such as hayfields and land grown with bushes, are marked by the following letters of the alphabet. In addition, separate land areas are marked by numbers. The double numbers were used at that time to denominate the stripped land system. It is worth mentioning that the 13th land plan of the village is dated 1789 and is special in that the cultivable three fields (marked XX) are not pictured by the households. The basis of its scale is a rope (1 rope = 43.2 meters or 30 ropes = 1 margas). This is not mentioned in the Senkoniai inventory, alas. However, from the contents, we can presume not a rope, but that valakas was used for measuring.